Impact of bloodstream infections caused by carbapenem-resistant Gram-negative pathogens on ICU costs, mortality and length of stay. Issue 2 (June 2019) - Kousouli, E.; Zarkotou, O.; Polimeri, K.; Themeli-Digalaki, K.; Pournaras, S.
Summary: Background: The aim of this study was to estimate the impact of bloodstream infections (BSIs) caused by carbapenem-resistant Gram-negative (CRGN) pathogens on hospital costs, mortality and length of stay (LOS). Methods: All patients hospitalized for ≥3 days in the Intensive Care Unit (ICU) of a tertiary-care general hospital from 1/1/2015 to 31/12/2017 were included in the study. A retrospective case-control study was performed in order to examine the difference in medical, pharmaceutical and operating costs, LOS and in-hospital mortality between patients with BSI caused by CRGN/without BSI (cases/controls, respectively). The statistical analysis was performed using the SPSS software (v23.0). Results: A total of 419 patients (67.5% males, median age 60.0 years) were included in the analysis (142 cases/277 controls); 10 patients with non-CRGN BSIs were excluded. Overall mortality was 33.7% (49.3/25.6% in cases/controls). The median LOS and total cost were 30.0 vs. 12.0 days and 20 359.1 vs. 8, 509.3 €, respectively, between patients with/without CRGN BSIs. After adjusting for baseline demographics, underlying disease severity and patients' specialties, CRGN BSIs remained a significant factor in mortality (odds ratio 2.9; 95% confidence interval 1.8–4.8; p <0.001). Additionally, CRGN BSIs seem to result in significantly prolonged LOS and extra cost per infected patient ( p <0.001). Conclusions: ICU patients with CRGN BSI are at increased risk for mortality and prolonged hospitalization and incur higher costs, imposing a heavy burden on healthcare system. Infection control strategies, considering also the cost-efficacy of interventions, are crucial in order to control the expansion of CRGN infections.